THE ANALYSIS OF STUDENTS’ ATTITUDE TOWARDS THE USE OF REFLECTIVE JOURNAL WRITING AS WRITING ACTIVITY - Yuli Herman; Nadya Shakila Feronika; Risza Dwiputri (ELP (Journal of English Language Pedagogy), 2020)
This study was aimed to know the attitude of students towards the use Reflective Journal Writing a writingactivity at the excellent classes of eighth grade students of SMPN 1 Solok in 2019/2020 academic year. The research method used in this study was quantitative descriptive. The population in this research was the excellent classes of eighth grade students of SMPN 1 Solok in 2019/2020 academic year. The total of population was 66 students of 2 classses The technique sample used was total sampling, where all the students in excellent classes, class VIII A and VIII B were included as the sample in the research. To get the data of the research, the researcher used questionnaire. The research design included a 5 point Likert-type questionnaire which were strongly agree (SA), Agree (A), Undecided (U), Disagree (D), and strongly Disagree (SD). In this case the researcher used 44 number of statements which based on 3 indicators of students’ attitude. The indicators of attitude were divided into cognitive, emotion and behavioral aspects. The finding of this research show the final percentage of students’ attitude towards reflective journal writing was 76%, it was classified as in the “very good” level. It means students had a very positive attitude towards the use of reflective journal writing as writing activity.